Kontribusi Alumni Perguruan Tinggi Barat terhadap Modernisasi Perguruan Tinggi Islam di Indonesia - Hijriana Rahmah Amelia; M. Nurul Humaidi (Global Education Journal, 2026)
The modernization of Islamic universities in Indonesia cannot be separated from the role of academics who have studied in Western universities since the 1970s. This study aims to examine the contribution of alumni of Western universities to the modernization process of Islamic Religious Universities (PTKI) in Indonesia, both in the aspects of scientific methodology, curriculum, institutional, and scientific integration discourse. This study uses a qualitative approach of the type of library research with historical-descriptive and analytical-critical methods, through content analysis of primary data in the form of works of related figures (Harun Nasution, Mukti Ali, Nurcholish Madjid, Azyumardi Azra, and others) as well as secondary data from books, scientific journals, and policy documents. The results of the study show that alumni of Western universities bring a rational, historical, and phenomenological approach that transforms Islamic studies from a dogmatic-normative nature to a critical-analytical nature, encourages the transformation of the curriculum from the focus of classical Islamic science to a more interdisciplinary one, and becomes a driver of the transfer of the status of a number of IAINs to UIN as a symbol of the integration of religious science and general science. These alumni also play a role in adapting the discourse on the Islamization of science and the paradigm of scientific integration-interconnection into the context of Indonesian Islamic higher education. Although there are concerns about the potential for a shift in the authenticity of classical Islamic science due to the dominance of the Western paradigm, the research findings conclude that the contribution of these alumni in general has a positive impact on strengthening the academic base, improving the quality of research, and openness of PTKI to the development of global science without losing its Islamic identity.